Uma abordagem sobre física das partículas para alunos do ensino médio - Silva, Hudson Batista da (2016)
This work is motivated by reflections on the introduction of Modern and Contemporary Physics in high school, because the physics teaching in this educational level has not adequately subsidized discussions about the technological advancements in the last two decades, against the recommendations of the National Curriculum Guidelines for Secondary Education. In this way, we believe that the lack of inclusion of more current issues in the teaching of Physics has caused a departure from the student to understand the world they live in. This world surrounded by technology and information, students hear about on topics such as black holes and the Big Bang on television, internet or in science fiction movies, but rarely in Physics class. The dissertative report still make explicit clements of the theory of Vygotsky, since our work suggests that the teacher is the element that will foster the process of teaching and learning and students an interactive and active subject in their knowledge-building process. The activities proposed here will inform we conduct the Standard Model as a theory that identifies the elementary particles and their interactions.